The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.7883/yoken1952.50.27
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Influenza Virus Rna in Peripheral Blood Mononuclear Cells of Influenza Patients

Abstract: SUMMARY:Gastroenteritis, arthralgaia and myalgia are frequently associated with influenza virus infections in humans.One explanation for these symptoms may be extrarespiratory transmission of virus by peripheral blood mononuclear cells (PBMC). We tried to detect genomic viral RNA of the nucleoprotein (NP) and H3 subtype hemagglutinin (HA) genes by the method of RT-PCR in PBMC of 18 children aged 1-14 who sufferred from an influenza outbreak in the Kansai district of Japan between December 1992 and February 199… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 7 publications
(5 reference statements)
1
19
0
Order By: Relevance
“…A number of studies searching for influenza viremia after the onset of illness have failed to detect virus, supporting the notion that influenza viremia is at most a rare event in the post-symptomatic period and if it exists, it is not generally sustained for long periods. However, recent studies employing highly sensitive PCR suggested transient viremia before onset of respiratory is not rare 33,34…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies searching for influenza viremia after the onset of illness have failed to detect virus, supporting the notion that influenza viremia is at most a rare event in the post-symptomatic period and if it exists, it is not generally sustained for long periods. However, recent studies employing highly sensitive PCR suggested transient viremia before onset of respiratory is not rare 33,34…”
Section: Discussionmentioning
confidence: 99%
“…22 These observations raise the possibility that antigenic cross-reactivity between influenzaspecific epitopes and resident plaque epitopes can develop within the microenvironment of an inflamed plaque. Such a mechanism of antigenic cross-reactivity is not uncommon in the course of longstanding chronic inflammatory processes, but apart from epitope mimicry, it cannot be ruled out that influenza A virus had been present in the plaques but later disappeared, eg, by eradication through the elicited inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…The serum level of IL‐6 is also higher in patients with acute influenza virus‐induced encephalopathy. 20 Furthermore, hyperactivated coagulation factors associated with DIC can participate in the pathogenesis. 21,22 …”
Section: Discussionmentioning
confidence: 99%